2022
DOI: 10.17085/apm.22145
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic care for electroconvulsive therapy

Abstract: Counselling and medication are often thought of as the only interventions for psychiatric disorders, but electroconvulsive therapy (ECT) has also been applied in clinical practice for over 80 years. ECT refers to the application of an electric stimulus through the patient’s scalp to treat psychiatric disorders such as treatment-resistant depression, catatonia, and schizophrenia. It is a safe, effective, and evidence-based therapy performed under general anesthesia with muscle relaxation. An appropriate level o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 99 publications
0
4
0
Order By: Relevance
“…The baseline characteristics of the included studies are found in Table 1 . Out of the included studies, two were of retrospective cohort nature ( 25 , 31 ), while the rest were clinical trials ( 27 30 , 32 , 37 , 40 ), some of which were crossover in nature ( 26 , 33 – 36 , 38 , 39 ). The included articles used etomidate and propofol as interventions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The baseline characteristics of the included studies are found in Table 1 . Out of the included studies, two were of retrospective cohort nature ( 25 , 31 ), while the rest were clinical trials ( 27 30 , 32 , 37 , 40 ), some of which were crossover in nature ( 26 , 33 – 36 , 38 , 39 ). The included articles used etomidate and propofol as interventions.…”
Section: Resultsmentioning
confidence: 99%
“…The crossover studies had a low risk of bias in general, as shown in Figure 3 . Two of the studies ( 33 , 35 ) had a low risk of bias in all assessing criteria and were deemed high quality. The remaining five studies were graded as moderate to good quality as they had problems with only 1 to 2 items of unclear risk.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the anesthetic provider should preoperatively evaluate the patients’ physical status and laboratory tests, and select anesthetics with neuromuscular blocking agents [ 2 , 3 ]. Nicotinic acetylcholine receptors (nAChRs) on the neuromuscular junction are up- or down-regulated in neuromuscular diseases, burns, and upper or lower motor nerve injury.…”
mentioning
confidence: 99%
“…TO THE EDITOR: We read with great interest the review by Joung et al [ 1 ] published in Anesthesia & Pain Medicine . We wish to describe our experience with different anesthetic drugs and techniques in a patient with catatonia undergoing multiple electroconvulsive therapy (ECT) sessions.…”
mentioning
confidence: 99%